2008
DOI: 10.1124/dmd.107.019596
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of Polychlorinated Biphenylols and UDP-Glucuronic Acid Concentrations in Channel Catfish Liver and Intestine

Abstract: ABSTRACT:Polychlorinated biphenylols (OH-PCBs) are potentially toxic polychlorinated biphenyl metabolites that can be eliminated by glucuronidation, catalyzed by UDP-glucuronosyltransferases (UGTs). OH-PCBs with a 3,5-dichloro-4-hydroxy substitution pattern have been detected in blood from humans and wildlife, suggesting slow elimination. In this study we assessed the glucuronidation of 4-OHPCBs with zero, one, or two chlorine atoms flanking the 4-hydroxyl group and zero to four chlorine atoms in the aphenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…LC-PCBs exhibit a high potential for metabolic conversion (Grimm et al 2015b; Robertson and Ludewig 2011). There is long-standing evidence for the ability of PCBs to be metabolized to their hydroxylated metabolites (OH-PCBs) by hepatic cytochrome P450 monooxygenases (Safe 1984), and the susceptibility of individual OH-PCBs to act as substrates for conjugation reactions mediated by sulfotransferases (SULTs) or UDP-glucuronosyl transferases (UGTs) has also been described (Dhakal et al 2012; Kester et al 2000; Liu et al 2006; Sacco et al 2008; Tampal et al 2002; Wang et al 2005; Wang et al 2006). Recent in vitro and in vivo studies revealed SULT-catalyzed sulfation of OH-PCBs as a major reaction in the metabolism of LC-PCBs in the rat (Dhakal et al.…”
Section: Introductionmentioning
confidence: 99%
“…LC-PCBs exhibit a high potential for metabolic conversion (Grimm et al 2015b; Robertson and Ludewig 2011). There is long-standing evidence for the ability of PCBs to be metabolized to their hydroxylated metabolites (OH-PCBs) by hepatic cytochrome P450 monooxygenases (Safe 1984), and the susceptibility of individual OH-PCBs to act as substrates for conjugation reactions mediated by sulfotransferases (SULTs) or UDP-glucuronosyl transferases (UGTs) has also been described (Dhakal et al 2012; Kester et al 2000; Liu et al 2006; Sacco et al 2008; Tampal et al 2002; Wang et al 2005; Wang et al 2006). Recent in vitro and in vivo studies revealed SULT-catalyzed sulfation of OH-PCBs as a major reaction in the metabolism of LC-PCBs in the rat (Dhakal et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the channel catfish, which spawn in late spring, there were seasonal differences in hepatic content of UDPGA, with average concentrations of 0.36 ± 0.07 nmol UDPGA/g liver (mean ± S.D., n = 7) in November/December and 0.13 ± 0.03 (n = 8) in May/June [72,73]. These concentrations approximate 0.36 and 0.13 mM and are lower than needed for maximal rates of glucuronidation of those substrates that have been studied in catfish liver, where values for UDPGA range from 0.28 to 0.7 mM [72,74].…”
Section: Glucuronidationmentioning
confidence: 98%
“…In the channel catfish, which spawn in late spring, there were seasonal differences in hepatic content of UDPGA, with average concentrations of 0.36 ± 0.07 nmol UDPGA/g liver (mean ± S.D., n = 7) in November/December and 0.13 ± 0.03 (n = 8) in May/June [72,73]. These concentrations approximate 0.36 and 0.13 mM and are lower than needed for maximal rates of glucuronidation of those substrates that have been studied in catfish liver, where values for UDPGA range from 0.28 to 0.7 mM [72,74]. While these findings suggest that in vivo rates of glucuronidation may be lower than reported from in vitro assays conducted under saturating conditions, and lower in catfish in May/June than November/December, no in vivo studies have been reported that could shed light on the effect of hepatic UDPGA concentration on rates of steroid glucuronidation in the intact fish.…”
Section: Glucuronidationmentioning
confidence: 98%
“…In vitro studies showed that several OH-PCBs were glucuronidated in catfish hepatic and intestinal microsomes (James and Rowland-Faux 2003; Sacco et al 2008). OH-PCBs with two chlorine atoms flanking the OH group were less efficiently glucuronidated than those with just one chlorine adjacent to the OH group (Sacco et al 2008).…”
Section: Biotransformation Of Pcbs By Fishmentioning
confidence: 99%